2014
DOI: 10.1103/physrevx.4.011031
|View full text |Cite
|
Sign up to set email alerts
|

Technical Advantages for Weak-Value Amplification: When Less Is More

Abstract: The technical merits of weak-value-amplification techniques are analyzed. We consider models of several different types of technical noise in an optical context and show that weak-value-amplification techniques (which only use a small fraction of the photons) compare favorably with standard techniques (which use all of them). Using the Fisher-information metric, we demonstrate that weak-value techniques can put all of the Fisher information about the detected parameter into a small portion of the events and sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
310
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 260 publications
(327 citation statements)
references
References 26 publications
6
310
1
Order By: Relevance
“…Refs. [13,24] argue that time-correlated noise, for example, renders the optimal estimator impractical due to computational complexity. This is not, by itself, a compelling argument for employing weak values, however: one must show that the entire weak value protocol, including the post processing, is not outperformed by a suitable benchmark strategy.…”
Section: Suboptimal Estimation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Refs. [13,24] argue that time-correlated noise, for example, renders the optimal estimator impractical due to computational complexity. This is not, by itself, a compelling argument for employing weak values, however: one must show that the entire weak value protocol, including the post processing, is not outperformed by a suitable benchmark strategy.…”
Section: Suboptimal Estimation Strategiesmentioning
confidence: 99%
“…Together these articles treat the most prevalent types of noise (including pixelation, detector jitter, and dephasing), and a similar approach can be used to analyse other imperfections. For instance, Jordan et al have claimed that for speci c noise models a weak-value-ampli ed tech-nique gives higher Fisher information than conventional methods [13]. By engineering these noise models articially, these predictions have been explored experimentally [14].…”
Section: Technical Noisementioning
confidence: 99%
“…The principal reason weak measurements have improved sensitivity is that they allow certain types of technical noise or other experimental limitations to be overcome, while still achieving the same sensitivity as ideal traditional measurement schemes [4,[24][25][26][27][28][29]. Previous theoretical work demonstrating the effectiveness of weak value amplification in reducing the negative effects of technical noise has been in what we term the weak value regime.…”
Section: Introductionmentioning
confidence: 99%
“…The price one pays for this amplification is the loss of a large fraction of events due to the post-selection. Nevertheless, the relevant information about the parameter in question is concentrated into these small number of events [2]. This technique has been adapted to optical metrology and has been successfully implemented in many experiments to precisely estimate various parameters, such as beam deflection, phase or frequency shifts.…”
Section: Introductionmentioning
confidence: 99%
“…Further, it has been shown that in comparison to a standard experimental technique, and given the presence of certain types of noise sources or technical limitations obscuring the measurement process, the weak value-type experiment can have better precision (even when using optimal statistical estimators), even though the detector only collects a small fraction of the light in the experiment [2]. There have also been a number of recent advances that propose to improve the intrinsic inefficiency of the post-selection.…”
Section: Introductionmentioning
confidence: 99%